2009
DOI: 10.1016/j.bmc.2008.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimalarial activity of new 4-amino-7-chloroquinolyl amides, sulfonamides, ureas and thioureas

Abstract: We report the synthesis and in vitro antimalarial activities of more than 50 7-chloro-4-aminoquinolylderived sulfonamides 3-8 and 11-26, ureas 19-22, thioureas 23-26, and amides 27-54. Many of the CQ analogues prepared for this study showed submicromolar antimalarial activity versus HB3 (chloroquine sensitive) and Dd2 (chloroquine resistant strains of P. falciparum) and low resistance indices were obtained in most cases. Systematic variation of the side chain length and introduction of fluorinated aliphatic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…We thus tested for a possible correlation between inhibition and antiplasmodial activity using a series of CQ analogues that are structurally similar yet span a wide range of antiplasmodial IC 50 s and LD 50 s ( Fig. 1; see Table S1 in the supplemental material) (24,(41)(42)(43). These analogues also span the effective monobasic, dibasic, and tribasic character and thus diverge in calculated VARs (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We thus tested for a possible correlation between inhibition and antiplasmodial activity using a series of CQ analogues that are structurally similar yet span a wide range of antiplasmodial IC 50 s and LD 50 s ( Fig. 1; see Table S1 in the supplemental material) (24,(41)(42)(43). These analogues also span the effective monobasic, dibasic, and tribasic character and thus diverge in calculated VARs (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis and chemical characterization of CQ analogues 1 to 5 have been reported previously (24,(41)(42)(43). Compounds 6 to 9 were synthesized as described below.…”
Section: Materials and Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolf et al reported in vitro antimalarial activities of the 4-amino-7-chloroquinolyl derived sulfonamides, ureas, thioureas, and amides [42]. Many of the analogues showed promising antimalarial activity and low resistance indices.…”
Section: Side Chain Modified 4-aminoquinolines (Figs 3e6)mentioning
confidence: 98%
“…a relatively less explored approach. The disclosure of ferrochloroquine (FQ,42), in which the carbon chain of CQ is replaced by the hydrophobic ferrocenyl group has been a welcome addition to organometallic antimalarial drugs[69,70]. This compound has been shown to be superior to CQ in both in vitro and in vivo tests.…”
mentioning
confidence: 98%